2009
DOI: 10.1111/j.1464-5491.2009.02808.x
|View full text |Cite
|
Sign up to set email alerts
|

Can peer educators influence healthy eating in people with diabetes? Results of a randomized controlled trial

Abstract: Aims To assess whether the Expert Patient Programme (EPP), adapted for people with Type 2 diabetes, can be used to promote healthy eating to improve glycaemic control.Methods Adults with Type 2 diabetes (n = 317) were randomized to receive either a diabetes-specific EPP (n = 162) or individual one-off appointments with a dietitian (control group) (n = 155). The diabetes-specific EPP followed the standard National Health Service programme although all participants in the group had diabetes only, rather than a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
71
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(75 citation statements)
references
References 12 publications
2
71
2
Order By: Relevance
“…10 In all but a few cases, the intervention was delivered by a single peer supporter. 3,5,10,14 None of the interventions appeared to involve other health care providers in the delivery of the peer-support component. However, all of the group-based interventions incorporated skills-development components such as goal setting, action-planning, and problem solving.…”
Section: Studies Includedmentioning
confidence: 81%
See 3 more Smart Citations
“…10 In all but a few cases, the intervention was delivered by a single peer supporter. 3,5,10,14 None of the interventions appeared to involve other health care providers in the delivery of the peer-support component. However, all of the group-based interventions incorporated skills-development components such as goal setting, action-planning, and problem solving.…”
Section: Studies Includedmentioning
confidence: 81%
“…[3][4][5][6][7][8][9][10][11][12][13][14][33][34][35][36] The 12 interventions included seven RCTs, four studies using a pre-/postdesign, 6,8,10,13 and one study using nonrandomized allocation of intervention and comparison groups. 14 Intervention delivery Face-to-face, group-based programs.…”
Section: Studies Includedmentioning
confidence: 99%
See 2 more Smart Citations
“…21,26,27,30,37 In contrast, the pooled effect size from the 7 studies with predominantly white, non-Hispanic participants showed no improvement in HbA 1c level with peer support interventions, with an SMD of -0.004 (95% CI, -0.153 to 0.144; P = .95; I 2 = 59.41%). 22,25,29,[31][32][33][34] The pooled effect in the subgroup of 3 studies with predominantly African American participants showed a similar effect size to that seen in the Hispanic subgroup but was not statistically significant, with an SMD of 0.25 (95% CI, -0.064 to 0.571; P = .11; I 2 = 58.60%). 23,24,28 The differences in effect sizes between ethnicity subgroups were statistically significant, with a between-group P value of .03.…”
Section: Subgroup Analyses Studies With Ethnic or Racial Predominancementioning
confidence: 78%